Platform Online Food Delivery: Antara Efisiensi dan Liberalisme dalam Muamalah - Zainuddin Zuhri (Fakultas Syariah dan Ekonomi Islam Institut Pesantren Mathali'ul Falah, 2026)
Online food delivery platforms have become a prominent phenomenon in contemporary muamalah practices, offering convenience and efficiency in food ordering and delivery. However, their emergence has generated debates within Islamic law, particularly regarding the alleged presence of multiple contracts (multi akad) considered inconsistent with sharia principles. This study aims to examine the ‘illah (effective legal cause) underlying the prohibition claims of online food delivery by analyzing the hadiths frequently used to support such arguments. The method employed is hadith criticism, including sanad and matn analysis, combined with a contextual approach to assess the relevance of these hadiths in light of technological developments and modern transaction systems. The findings indicate that online food delivery practices, especially those using the cash on delivery (COD) system, do not contain the ‘illah referred to in the relevant hadiths, such as elements of riba, gharar, or prohibited contract combinations. The COD mechanism, including the courier’s role in advancing payment to the seller, is better understood as part of an operational system aimed at achieving transactional efficiency rather than as an independent debt contract. Therefore, online food delivery should not be categorized as a form of liberalism in muamalah, but rather as an efficient and adaptive practice within the framework of Islamic commercial law.